Evaluación serológica e histopatológica de la enfermedad de gumboro en la región del Sumapaz (Cundinamarca, Colombia). (1988)
Twenty three flocks from commercial broilers, without vaccination plans against IBD (Gumboro) at the Sumapaz area (Cundinamarca, Colombia), were evaluated under serological and histopathological studies for this entity. A serologic prevalence of 92.0% was found in the area under study, and according to the records the morbility and mortality rates were 47.5 and 12.0%, respectively. It was also established that the mortality rate generally decreases as the age of animals increases. Histopathological findings showed a good correlation with the serological studies.